Electronic portfolio as a knowledge management tool: a comparative analysis - Zainal Abidin, Wardah (2013)
Traditionally, electronic portfolio tools focused mainly on the presentation of information, with an archive of digital data that are derived from the associated purpose of the presentation. Today, new electronic portfolio tools include digital environments for assembling and managing documents and all forms of media in a digital archive, and/or software applications for assembling and sorting portions of that archive for a particular purpose. This shares many features with knowledge management tools. Central to both tools is the knowledge creation stage. Based on our experiences of using electronic portfolio, this paper explores the potential use of electronic portfolio as a knowledge management (KM) tool for knowledge workers in organizations. Salient features of characteristics of KM tools are studied and these are matched against various electronic portfolio features. The paper then shows how the electronic portfolio can be used as a means to tackle the challenges faced at the individual context of the knowledge creation phase.